Brain Functional and Structural Signatures in Parkinson’s Disease - Liu, Chunhua; Jiang, Jiehui; Zhou, Hucheng; Zhang, Huiwei; Wang, Min; Jiang, Juanjuan; Wu, Ping; Ge, Jingjie; Wang, Jian; Ma, Yilong; Zuo, Chuantao (Frontiers in Aging Neuroscience, 2020)
The aim of this study is to explore functional and structural properties of abnormal brain networks associated with Parkinson’s disease (PD). 18F-Fluorodeoxyglucose positron emission tomography (18F-FDG PET) and T1-weighted magnetic resonance imaging from 20 patients with moderate-stage PD and 20 age-matched healthy controls were acquired to identify disease-related patterns in functional and structural networks. Dual-modal images from another prospective subject of 15 PD patients were used as the validation group. Scaled Subprofile Modeling based on principal component analysis method was applied to determine disease-related patterns in both modalities, and brain connectome analysis based on graph theory was applied to verify these patterns. The results showed that the metabolic pattern was characterized by relative increased metabolic activity in pallidothalamic, pons, putamen, and cerebellum, associated with metabolic decreased in parietal-occipital areas. The structural pattern was characterized by relative decreased gray matter volume in pons, transverse temporal gyrus, left cuneus, right superior occipital gyrus and right superior parietal lobule, associated with preservation in gray matter volume in pallidum and putamen. In addition, both patterns were verified in the connectome analysis. The findings suggest that significant overlaps between metabolic pattern and structural pattern provide new evidence for elucidating the neuropathological mechanisms of PD.